A Case of Bilateral Optic Nerve Head Drusen-Induced Inferior Altitudinal Hemianopsia. (August 2015) - Tanaka, Hidenori; Shimada, Yoshiaki; Nakamura, Akira; Tanikawa, Atsuhiro; Horiguchi, Masayuki
ABSTRACT The current case involved a 59-year-old woman who was referred to our hospital with bilateral optic nerve abnormality and gradually progressive bilateral inferior visual field defects. An ophthalmological examination revealed superficial optic nerve head drusen (ONHD) and bilateral inferior altitudinal hemianopsia, but no intracranial lesions. The results of an angiogram revealed no evidence of retinal vascular occlusion or anterior ischaemic optic neuropathy (AION). Prior reports suggested that drusen-induced hemianopsia was slowly progressive but that ONHD-induced AION caused acute altitudinal hemianopsia, which led us to the diagnosis of bilateral drusen-induced altitudinal hemianopsia.